2007
DOI: 10.1007/s00468-007-0151-1
|View full text |Cite
|
Sign up to set email alerts
|

Cold in the common garden: comparative low-temperature tolerance of boreal and temperate conifer foliage

Abstract: Because they maintain green foliage throughout the winter season, evergreen conifers may face special physiological challenges in a warming world. We assessed the midwinter low-temperature (LT) tolerance of foliage from eight temperate and boreal species in each of the genera Abies, Picea, and Pinus growing in an arboretum in Trondheim, Norway, using relative electrolyte leakage (REL) as an index of cell injury. Relatively LT sensitive species came from temperate coastal and Mediterranean environments and disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…Pinus sylvestris is generally considered a more coldtolerant species compared to P. nigra, based on their distributional areas and confirmed by experimental data (Strimbeck et al, 2007). However our experiment showed a very similar response of secondary needles, with even a slightly higher frost tolerance for P. nigra.…”
Section: Ecological Correlations and Evolutionary Implicationssupporting
confidence: 87%
“…Pinus sylvestris is generally considered a more coldtolerant species compared to P. nigra, based on their distributional areas and confirmed by experimental data (Strimbeck et al, 2007). However our experiment showed a very similar response of secondary needles, with even a slightly higher frost tolerance for P. nigra.…”
Section: Ecological Correlations and Evolutionary Implicationssupporting
confidence: 87%
“…Despite numerous reports of a correlation of plant freezing tolerance with tissue concentrations of raffinose (Klotke et al 2004;Strimbeck et al 2007;Grant et al 2009), it was demonstrated that raffinose appears not essential in the freezing tolerance of A. thaliana, since the raffinose synthase mutant RS14 defective in the single copy raffinose synthase gene At5g40390 showed the same freezing tolerance as Col-0 wild type plants (Zuther et al 2004). In the study by Zuther and colleagues, the widely accepted EL test was applied to assess freezing damage of excised leaves subjected to freeze-thaw cycles.…”
Section: Discussionmentioning
confidence: 95%
“…A prominent example for this ambiguity is the raffinose family oligosaccharides (RFO), a group of sugars derived from sucrose by galactosyl extension (Keller and Pharr 1996;Peterbauer and Richter 2001). For the simplest representative of RFO, the trisaccharide raffinose, a correlation of the tissue concentrations with freezing tolerance has been demonstrated for plants as diverse as the woody conifers (Strimbeck et al 2007) and the herbaceous crucifer Arabidopsis thaliana (Klotke et al 2004;Rohde et al 2004). While a potential for the protection of membranes against damage during drying, which is a side effect of ice crystal formation in intercellular spaces, has been demonstrated for raffinose in vitro (Hincha et al 2003), it has also been postulated that it may act as a radical scavenger helping the plant to detoxify reactive oxygen species that accumulate at low temperatures (Nishizawa et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, extreme cold, or mini mum winter temperature, was mentioned as the principal factor determining the northern limits of the natural tree habitat because it relates to injury or death of organs such as twigs (Matsui et al 2004a,b, Sakai 1978, Sakai et al 1979. Strimbeck et al (2007) stated that an understanding of the degree and mechanisms of low temperature tolerance is important in predicting the effects of climate change on tree and forest health and productivity. Therefore, some studies used both the WI and MTC to predict the distribution change of particular species due to climate change (Matsui et al 2004a,b, Choi et al 2010b.…”
Section: Introductionmentioning
confidence: 99%